Assessment of Real-World Use of Behavioral Health Mobile Applications by a Novel Stickiness Metric - Carlo, Andrew D. (JAMA Netw Open, 2020)
This cross-sectional study uses a novel “stickiness” measure to evaluate which mobile applications for smoking cessation, meditation, and other behavioral health areas are associated with long-term engagement.